EP159/#428 Real-world experience and common adverse events when using combination lenvatinib and pembrolizumab for the treatment of recurrent uterine cancer. (4th December 2022) - Zammarrelli, William; Espino, Kevin; Yeoshoua, Effi; Ehmann, Sarah; Rubinstein, Maria; Green, Angela; Makker, Vicky
Abstract : Objectives: To evaluate the toxicity of combination lenvatinib plus pembrolizumab for the treatment of recurrent uterine cancer in a real-world setting. Methods: We retrospectively reviewed patients with a diagnosis of uterine cancer who were treated with lenvatinib plus pembrolizumab at our institution between 9/1/21–1/31/22. Adverse events were manually extracted through chart review and graded according to Common Terminology Criteria for Adverse Events Version 5.0. Results: Forty-three patients were treated with combination lenvatinib plus pembrolizumab with a median age of 67 years (range, 54–85). The most common histologies were serous (35%), endometrioid (23%), and carcinosarcoma (21%). Lenvatinib plus pembrolizumab was second-line treatment in 13 patients (30%), third-line treatment in 15 patients (35%), and fourth-line treatment or beyond in 15 patients (35%). The median number of cycles received was 8 (range, 1–37). Nineteen patients (44%) had a primary dose reduction and 17 patients (40%) required at least one lenvatinib dose reduction during treatment. Three patients (7%) discontinued lenvatinib and 1 patient (2%) discontinued pembrolizumab for intolerance or adverse event. Forty-one patients (98%) experienced an adverse event; 36 (86%) experienced a grade 3 or higher adverse event. The most common grade 3 or higher adverse events were hypertension, anemia, weight loss, fatigue, and thrombocytopenia. Conclusions: In clinical practice, adverse events associated with combination lenvatinib plus pembrolizumab are common and comparable to the experience in KEYNOTE-775. Primary dose reductions were common and most patients continued treatment. Efficacy results are forthcoming.